The Effectiveness of Using Shadowing Technique Towards Students’ Pronunciation Skill at Twelfth Grade Students in Senior Highschool Number 02 Muaro Jambi - Rifaldo Chandra Ardana; Suyadi Suyadi; Yurni Yurni (Universitas Batanghari Jambi, 2023)
This research was made to figure out if there is an improvement after using Shadowing Technique that applied to twelfth grade students in senior high school number 02 Muaro Jambi. This research used Quantitative method with Quasi-Experimental design and using SPSS as data analysis technique. The total population in this school was 239 students. In this research, researcher use one experimental group and one control group. The experimental group that chosen in this research was XII MIPA 2 and XII IPS 2 as the control group with the total of 61 samples (30 students for experimental group and 31 students for control group). The technique that used in this research to collect the data was students must immediately follow the words that speaker said. The results that were found in this research are: (1) Students pronunciation skill taught by using Shadowing Technique now can pronounce the words in English pronunciation and less using Indonesian pronunciation (2) Some students’ who categorized in poor pronunciation skill now become average criteria after the treatment of Shadowing Technique. Therefore, at the end of this research, there is an improvement of students’ pronunciation skill after using Shadowing Technique.